Testing the Relationships between Energy Consumption, CO₂ emissions and Economic Growth in 24 African Countries: a Panel ARDL Approach - Simplice A. Asongu; Ghassen El Montasser; Hassen Toumi (African Governance and Development Institute (AGDI), 2015)
This study complements existing literature by examining the nexus between energy consumption (EC), CO2 emissions (CE) and economic growth (GDP) in 24 African countries using a panel ARDL approach. The following findings are established. First, there is a long run relationship between EC, CE and GDP. Second, a long term effect from CE to GDP and EC is apparent, with reciprocal paths. Third, the error correction mechanisms are consistently stable. However, in cases of disequilibrium only EC can be significantly adjusted to its long run relationship. Fourth, there is a long-run causality running from GDP and CE to EC. Fifth, we find causality running from either CE or both CE and EC to GDP and inverse causal paths are observable. Causality from EC to GDP is not strong, which supports the conservative hypothesis. Sixth, the causal direction from EC to GDP remains unobservable in the short term. By contrast, the opposite path is observable. There are also no short-run causalities from GDP, or EC, or EC and GDP to EC. Policy implications are discussed.
Keywords: C52; O40; O55; Q43; Q50; 330; Energy consumption; CO2 emissions; Economic growth; Africa